A global perspective of social justice leadership for school principals - Angelle, Pamela S. (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
Within education there have been some notable attempts to frame social justice in ways that can help to explain and understand the practices of those working in schools, especially school leaders. The research contained in this book seeks to enhance our understanding of school leaders' actions as they work to promote socially just practices and/or outcomes in a range of different national contexts. The unique nature of this research is that studies took place in numerous schools across the globe in a variety of contexts yet utilized the same research protocols. This has allowed the researchers to draw conclusions at an international level about social justice decision making, the supports and barriers brought on school leaders by national policy and mandates, and the essential nature of context in the work of social justice leadership. The audience will include scholars on a global scale, given that cases in the book include authors and principals from around the world. The book can also serve as a text for leadership preparation courses as well as courses in social justice, research design, and qualitative research methodologies. Courses in human relations and communication can use the content as examples of the negotiations and challenges of teamwork in international settings. A primary audience for the book is system/school level leaders in contexts and communities throughout the world for understanding comparative leadership and social justice decision making. Current principals will find the cases useful as reflexive tools for their own work. Educational leaders, educational reformers, and policy makers will benefit from this book as they seek to understand the impact of their work and its influence on promoting equity in schools across the globe.